Analisis Proses Dewatering Konsentrat Mineral pada PT. Freeport Indonesia - Novriany Amaliyah (Jurnal Teknik Mesin Sinergi, 2021)
A concentrate treatment process is needed to improve the quality of the concentrate. Processing of copper minerals by drying concentrate or dewatering. The slurry concentrate dewatering process is intended to inhibit the rate of damage to the concentrate, and it is easy to distribute the concentrate through shipping. PT. Freeport Indonesia has 2 types of machines for the dewatering slurry process, Rotary Dryer and VPA (Vertical Pressure Airblow). The dryer dries the slurry by evaporating the water in the slurry through a combustion process with temperatures reaching 1500o F. While the VPA machine only uses membrane compression and compressed air to dry the concentrate. A comparison of the power requirements needed to dry the slurry on the two machines is done to determine the effectiveness and energy needs of the input. The results obtained in this study that dryer requires an average power of 84.31 kW to dry every 1-ton slurry, and VPA machines only use power with an average of 0.0078 kW in every 1-ton slurry